Estimation of properties of mixed waste cooking oil for production of biodiesel - S. V. S. R. Krishna, B.; B.K, Shivaraj (International Journal of Engineering and Technology, 2018)
The major drawback of production of biodiesel in large scale is the cost of raw materials. Raw material source of biodiesel is mostly plant oil (Jatropha, Pongamia, Mahua, Neem, Cotton seed oil etc.) which requires large land area to grow. One of the best methods to reduce the production cost of biodiesel is to employ low quality feedstock, for instance waste cooking oil (WCO). This also solves the disposal problem of WCO. This is socioeconomic and environment friendly, it does not compete with edible oil resources. This study represents the biodiesel production from mixed waste cooking oil. Waste cooking oil collected from different hotels around Manipal, Udupi district of Karnataka State, and India. Collected WCO from various sources (from palm oil and sunflower oil users) have different physical and chemical properties. These WCO has mixed in different ratios ie. 50:50, 75:25 and 25:75 to reduce free fatty acid content of WCO without any chemical pre-treatment. Physio-chemical properties of mixed WCO has been carried out.Â